Chiral calamitic organosiloxane liquid crystals with tunable properties - Karaagac, Burcu; Akdas-Kilic, Huriye; Vardar, Deniz; Jeannin, Olivier; Camerel, Franck; Ocak, Hale; Eran, Belkiz Bilgin (ROYAL SOC CHEMISTRY, 2025)
A series of dissymmetric chiral calamitic liquid crystals were designed and synthesized, featuring a central phenyl-benzoate core linked via ester bridges to a chiral (S)-3,7-dimethyloctyloxy chain at one terminus and a biphenyl carboxylate with an undecenyloxy alkyl tail at the other. Multi-step synthetic procedures, including a key hydrosilylation step, enabled the construction of siloxane-bridged dimers, incorporating two identical chiral rod-like units tethered via a disiloxane spacer. These derivatives were fully characterized using 1H, 13C, and 29Si NMR, mass spectrometry, and elemental analysis. The liquid crystalline and thermal behaviors of all compounds were systematically studied using polarizing optical microscopy (POM), differential scanning calorimetry (DSC), X-ray diffraction (XRD), and electro-optic (EO) techniques. All synthesized mesogens exhibited liquid crystalline phases. Notably, the vinyl-terminated siloxane derivative displayed both a stable chiral smectic C (SmC*) phase and an enantiotropic chiral nematic (N*) phase. The siloxane-bridged dimer showed an expanded smectic mesophase range, alongside the N* phase, underscoring the impact of siloxane connectivity on mesophase stability and organization. Furthermore, by inverting the orientation of one carboxylate linker within the molecular architecture, a broader and singular chiral SmC* phase was achieved, highlighting the subtle yet significant influence of structural asymmetry on mesomorphic behavior.
Keywords: MESOMORPHIC PROPERTIES; THERMAL-STABILITY; PHASE-TRANSITIONS; CORE; ORIENTATION; DIMERS; SERIES; POLAR; Chemistry